Accuracy of clinical tests in the diagnosis of anterior cruciate ligament injury: a systematic review - Swain, Michael; Henschke, Nicholas; Kamper, Steven J.; Downie, Aron S.; Koes, Bart W.; Maher, Chris G. (Chiropractic & manual therapies, 2014)
Numerous clinical tests are used in the diagnosis of anterior cruciate ligament (ACL) injury but their accuracy is unclear. The purpose of this study is to evaluate the diagnostic accuracy of clinical tests for the diagnosis of ACL injury.
Gesehen am 12.02.2021